Technologies for metadata management in scientific articles (2015)
(Eng) The use of Semantic Web technologies has been increasing, so it is common using them in different ways. This article evaluates how these technologies can contribute to improve the indexing in articles in scientific journals. Initially, there is a conceptual review about metadata. Later, studying the most important technologies for the use of metadata in Web and, this way, choosing one of them to apply it in the case of study of scientific articles indexing, in order to determine the metadata based in those used in impact research journals, and building a model for indexing scientific articles using Semantic Web technologies.